Assessing digital transformation maturity in higher education institutions: a correlational analysis by actors and dimensions - Bravo-Jaico, Jessie; Maquen-Niño, Gisella Luisa Elena; Germán, Nilton; Valdivia, Carlos; Alarcón, Roger; Aquino, Janet; Serquén, Oscar (Frontiers in Computer Science, 2025)
This study evaluated the maturity of Digital Transformation (DT) in a Higher Education Institution (HEI), analyzing how teachers, students, administrators and managers perceive various dimensions of DT, including Sociocultural, Teaching-Learning, Digital Governance, Research-Innovation, Academic Management, Administrative Management, Institutional Image-Marketing and University Extension. A quantitative approach was used, applying four structured surveys validated by experts to 338 participants from a HEI, which were processed by applying Spearman’s correlation analysis. It was found that digital maturity varies significantly according to the actor and the dimension considered. For teachers, Digital Governance shows strong links with University Extension and Research, suggesting that digitalization enhances both social projection and academic collaboration. Students perceive the importance of Institutional Image-Marketing in creating a positive presence of the institution. As for administrative staff, administrative management is strongly related to Institutional Image, reflecting the impact of internal efficiency on public perception. Managers, on the other hand, emphasize the role of University Extension in strengthening institutional prestige. The study concludes that DT in HEIs is multifactorial and recommends adopting customized digital maturity strategies that respond to the needs of each actor, thus facilitating an effective and sustainable digital transformation.